Transforming Your Business with AWS Getting the Most Out of Using AWS Cloud to Modernize and Innovate Your Digital Services - Abdoulaye, Philippe (John Wiley & Sons, Inc., 2022)
Expert guidance on how to use Amazon Web Services to supercharge your digital services business In Transforming Your Business with AWS: Getting the Most Out of Using AWS to Modernize and Innovate Your Digital Services, renowned international consultant and sought-after speaker Philippe Abdoulaye delivers a practical and accessible guide to using Amazon Web Services to modernize your business and the digital services you offer. This book provides you with a concrete action plan to build a team capable of creating world-class digital services and long-term competitive advantages. You'll discover what separates merely average digital service organizations from the truly outstanding, as well as how moving to the cloud will enable your business to deliver your services faster, better, and more efficiently. This book also includes: A comprehensive overview of building industry-leading digital service delivery capabilities, including discussions of the development lifecycle, best practices, and AWS-based development infrastructure Explanations of how to implement a digital business transformation strategy An exploration of key roles like DevOps Continuous Delivery, Continuous Deployment, Continuous Integration, Automation, and DevSecOps Hands-on treatments of AWS application management tools, including Elastic Beanstalk, CodeDeploy, and CodePipeline Perfect for executives, managers, and other business leaders attempting to clarify and implement their organization's digital vision and strategy, Transforming Your Business with AWS is a must-read reference that answers the "why" and, most importantly, the "how," of digital transformation with Amazon Web Services.